SPATIAL PARAMETERS OF STATOGRAMS IN DIAGNOSING PATHOLOGIES OF THE HUMAN LOCOMOTOR SYSTEM - Pavlov, Sergii; Bezsmertnyi, Yurii; Iaremyn, Stanislav; Bezsmertna, Halyna (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2020)
The analysis of the spatial parameters of statograms in terms of the projection area of the common center of mass (CCM) in single and double support was performed, along with the magnitude of the total maximum area of the statogram and its relation to the area of the projection spot for each type of standing, and the area of the statogram according to the mathematical expectation. The high sensitivity of the spatial parameters of statograms is indicated by the values of the CCM spot plane in the case of single support, the ratio of the planes, and the angular asymmetry. The analysis of the parameters of statograms showed that for all types of standing volunteers of the control group, the area of the projection spot of the CCM was the smallest in both two-pronged standing, and in single support standing. In patients with osteochondrosis and with coxarthrosis (CA), the area of the spots was much larger, with a statistically significant difference observed in single support (p < 0.05). The ratio of the planes was statistically different between groups (р = 0.043): in the control group it was the maximum (0.38), which reflects the highest ability to maintain equilibrium, and the minimum (0.25) – in the group of patients with CA. An analysis of variance revealed a significant difference (p = 0.025) of asymmetry in body angle between the study groups. The angle of the body rotation in the case of single support is not statistically different in the study groups (p = 0.294), but this indicator can be considered as prognostic in terms of the diagnosis of pathology of the musculoskeletal system.